Trends and Features of FinTech Management Processes Evolution During the Global Pandemic - Makarenko, Anastasiya B.; Tataryntseva (Kurbatova), Yu. L.; Kochetova, Tatiana I. (Одеський національний політехнічний університет, 2022)
Nowadays functioning of the national economy demands the country inclusion in the global processes of financial technology management. This article summarizes the key approaches to understanding the evolution of the use of financial technologies during the global pandemic. The growing influence of financial technologies on all spheres of life and economy is proved. Conclusions are drawn from the results of the research on the benefits of financial technologies application, in particular during the COVID pandemic.

Функціонування національної економіки в ринкових умовах передбачає включення країни у світові процеси управління фінансовими технологіями. У статті узагальнено ключові підходи до розуміння еволюції використання фінансових технологій в сучасних умовах під час світової пандемії. Доведено зростаючу роль впливу фінансових технологій на усі сфери життя та економіки. Зроблено висновки з результатів дослідження, щодо переваг використання фінансових технологій, зокрема під час COVID.
Тенденції та особливості розвитку процесів управління FinTech під час глобальної пандемії
Keywords: management; financial technologies; finance; trends; financial strategy; економіка; фінансові технології; коронавірус; епідемія; управлінська діяльність